2017
DOI: 10.20344/amp.8228
|View full text |Cite
|
Sign up to set email alerts
|

Partial Red Blood Cell Exchange in Children and Young Patients with Sickle Cell Disease: Manual Versus Automated Procedure

Abstract: Automated red blood cell exchange is safe and well tolerated. It permits a higher sickle hemoglobin removal efficacy, better volume status control and iron-overload avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
0
20
2
Order By: Relevance
“…Automated exchange was associated with a lower increase in ferritin than manual exchange as automatic exchange transfusion is an isovolumetric process that can accomplish a larger, more efficient exchange of RBCs. 8,9 Our results are distinctly different from prior single center studies that have demonstrated automatic exchange transfusion limits excessive iron stores [10][11][12][13][14][15] because our primary results did not have to adjust for treatment with or adherence to chelation therapy and intra-individual differences in absorption of chelation. Even when we included those that received some chelation therapy in the first year, there was no significant difference in the primary finding that automated RBC exchange transfusion is associated with a lower rise of ferritin levels when compared to manual exchange or simple blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Automated exchange was associated with a lower increase in ferritin than manual exchange as automatic exchange transfusion is an isovolumetric process that can accomplish a larger, more efficient exchange of RBCs. 8,9 Our results are distinctly different from prior single center studies that have demonstrated automatic exchange transfusion limits excessive iron stores [10][11][12][13][14][15] because our primary results did not have to adjust for treatment with or adherence to chelation therapy and intra-individual differences in absorption of chelation. Even when we included those that received some chelation therapy in the first year, there was no significant difference in the primary finding that automated RBC exchange transfusion is associated with a lower rise of ferritin levels when compared to manual exchange or simple blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 77%
“…As opposed to simple transfusion which involves the administration of RBC units that contain approximately 250 mg of iron per unit, phlebotomy during exchange transfusion removes some iron with the removal of RBCs. Automated exchange was associated with a lower increase in ferritin than manual exchange as automatic exchange transfusion is an isovolumetric process that can accomplish a larger, more efficient exchange of RBCs 8,9 . Our results are distinctly different from prior single center studies that have demonstrated automatic exchange transfusion limits excessive iron stores 10‐15 because our primary results did not have to adjust for treatment with or adherence to chelation therapy and intra‐individual differences in absorption of chelation.…”
Section: Discussioncontrasting
confidence: 68%
“…Regarding the adverse outcome events due to either red cell exchange procedures, a random effects model analysis from seven included studies [3, 7, 8, 10, 13, 21, 22] did not reveal any significant increase in the risk; however, there was a trend of increased risk of adverse events in the aRBX group. We segregated these adverse events into procedure‐related and catheter‐related events and performed a separate meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although hydroxyurea has shown clinically proven efficacy with significant improvement of VOC and ACS, many breakthrough trials have shown that chronic transfusion therapy can prevent stroke, reducing the frequency of vaso-occlusive pain crisis and acute chest syndrome-related hospitalizations as well as other chronic complications related to SCD [4][5][6]. Blood transfusion in SCD mainly aims to correct anaemia and improve the oxygen-carrying capacity, as transfusion of normal red blood cells (RBCs) carrying normal haemoglobin A (HbA) dilutes the circulating level of sickled HbS, thus diminishing impaired erythropoiesis, haemolysis and vaso-occlusive events, which are major contributors to the complications of SCD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with manual RCE, 3 studies reported increased red cell unit use with automated RCE, 95,98,100 whereas 1 study reported a slight decrease in red cell unit use. 97 Rationale and key driver for recommendation.…”
Section: Remarks: Cmentioning
confidence: 98%